2012
DOI: 10.4103/2153-3539.100154
|View full text |Cite
|
Sign up to set email alerts
|

Experience with CellaVision DM96 for peripheral blood differentials in a large multi-center academic hospital system

Abstract: Context and Aims:Rapid, accurate peripheral blood differentials are essential to maintain standards of patient care. CellaVision DM96 (CellaVision AB, Lund, Sweden) (CV) is an automated digital morphology and informatics system used to locate, pre-classify, store and transmit images of platelets, red and white blood cells to a trained technologist who confirms or edits CV cell classification. We assessed our experience with CV by evaluating sensitivity, specificity, positive predictive value and negative predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 9 publications
1
27
0
Order By: Relevance
“…It has previously been shown that the DM96 is faster than manual smear examination an aspect confirmed in our internal departmental validation studies. [9121415] This is of particular importance as labor is one of the major expenditures in the laboratory. In addition, digitized images provide many advantages compared to manual slide microscopy.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been shown that the DM96 is faster than manual smear examination an aspect confirmed in our internal departmental validation studies. [9121415] This is of particular importance as labor is one of the major expenditures in the laboratory. In addition, digitized images provide many advantages compared to manual slide microscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Our misclassification rate was higher than that described previously by Rollins-Raval, Raval and Contis, who assessed the performance of the DM96 over a six-month period at three separate sites. 14 The number of unidentified cells in that study was ~1% and the number of misclassified cells ranged from 4.6% – 12.7%. The higher misclassification rate in our study is likely a product of the large number of specimens containing malignant cells and selection of a large number of samples with extreme WCCs for the purpose of evaluating the analyser.…”
Section: Discussionmentioning
confidence: 72%
“…[ 65 105 106 107 ] In human and veterinary diagnostic cytopathology, proprietary, neural-network-based pre-classification systems arewidely used, particularly for hematology applications. [ 108 109 ] Most recently, two AI-based decision support tools in CDP have gained FDA Breakthrough Device designation: Paige. AI in 2019 for cancer histology[ 5 ] and 4D Q-plasia OncoReader Breast in 2020 for breast cancer histology.…”
Section: Achine L Earning a Pplications I N T Oxicologic mentioning
confidence: 99%